2016
DOI: 10.1186/s13049-016-0201-z
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of cognitive aids for emergency airway equipment preparation in a Paediatric Emergency Department

Abstract: BackgroundSafety of emergency intubation may be improved by standardising equipment preparation; the efficacy of cognitive aids is unknown.MethodsThis randomised controlled trial compared no cognitive aid (control) with the use of a checklist or picture template for emergency airway equipment preparation in the Emergency Department of The Royal Children’s Hospital, Melbourne.ResultsSixty-three participants were recruited, 21 randomised to each group. Equal numbers of nursing, junior medical, and senior medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 24 publications
1
19
0
2
Order By: Relevance
“…Standardising the kit dump process and the use of cognitive aids reduces the number of decisions an operator must make, ensures equipment availability and has been recommended as a strategy for reducing error (Schnittker et al, 2018;Benger & Hopkinson, 2011;Marshall, 2013;Lockey et al, 2014;Long et al, 2016;Chrimes, 2016). We observed that those using the SCRAM bag performed a kit dump significantly quicker.…”
Section: Discussionmentioning
confidence: 79%
“…Standardising the kit dump process and the use of cognitive aids reduces the number of decisions an operator must make, ensures equipment availability and has been recommended as a strategy for reducing error (Schnittker et al, 2018;Benger & Hopkinson, 2011;Marshall, 2013;Lockey et al, 2014;Long et al, 2016;Chrimes, 2016). We observed that those using the SCRAM bag performed a kit dump significantly quicker.…”
Section: Discussionmentioning
confidence: 79%
“…This is especially relevant for intubations performed in the prehospital setting or during retrievals. Lack of familiarity with available equipment or its location may increase operator cognitive load, may delay planning for initial and subsequent intubation attempts, and may contribute to errors of omission or commission during emergency airway management . Team and equipment ergonomics may contribute to situational difficulties, as may behavioral factors in young or agitated children.…”
Section: What Are the Contributors?mentioning
confidence: 99%
“…Strategies to address this issue include standardization and simplification of airway equipment, and locating airway equipment in identical trolleys in all critical care areas . In addition, the use of cognitive aids in the forms of templates or checklists may help standardize specific equipment and its layout . Team and equipment ergonomics may contribute to situationally difficult airways, particularly in young children and infants, whose small size relative to that of the treating team significantly limits patient access.…”
Section: Is There a Solution?mentioning
confidence: 99%
“…In recent years, there has been a keen interest in how checklists and other cognitive aids can help clinicians during clinical crises. Studies from anaesthesia , and emergency medicine have shown that displaying cognitive aids during emergencies reduces omissions, time to perform tasks and improves team skills, communication and performance in most instances . In research where no difference was found, the cognitive aids are almost always found to have been introduced without education or have flaws in their physical design .…”
mentioning
confidence: 99%